A thermal expansion measurement system using a high-temperature unguided half-bridge displacement transducer - (:unkn) unknown (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2005)
In this paper, a temperature and vacuum rate controllable furnace, which is suitable for thermal expansion measurement of metal samples having predefined standard dimensions, is designed and realized.
Keywords: displacement transducer; linearly variable differential transformer (LVDT) signal conditioner; PC-based data acquisition; thermal expansion measurement; vertical dilatometer